The RasGAP Gene, RASAL2, is a Tumor and Metastasis Suppressor - McLaughlin, Sara Koenig (2013)
RAS genes are commonly mutated in cancer; however, RAS mutations are rare in breast cancer, despite the fact that Ras and ERK are frequently hyperactivated. Here we report that the RasGAP gene, RASAL2, functions as a tumor and metastasis suppressor. RASAL2 is mutated or suppressed in human breast cancer and RASAL2 ablation promotes tumor growth, progression, and metastasis in mouse models. In human breast cancer RASAL2-loss is associated with metastatic disease, low RASAL2 levels correlate with recurrence of luminal B tumors, and RASAL2 ablation promotes metastasis of luminal mouse tumors. Additional data reveal a broader role for RASAL2 inactivation in other tumor-types. These studies highlight the expanding role of RasGAPs and reveal an alternative mechanism of activating Ras in cancer.